Թադեւոս Տոնոյեան. աշխարհ, որ ընդլայնում է գոյութեան սահմանները (Ա.) - Գրիգորեան, Վաչագան (տպ. Atlas)
Thadevos Donoyan is one of the unique figures of 1990-2000 Armenian literature. His poetry reflects the changes that have taken place in contemporary Armenian poetry. These changes include both the vector and the limits of what is being said. It is not interesting anymore to engulf the reader in “beautiful lies”. Indeed, poetry has cast out the naturalist picture and the traditional poetic perception of time and space. Traditional poetry used to generate its poetic world through external scenes, and by giving meanings to phenomena which lied outside the poet. Contemporary poetry has freed itself from these and has the inner world as its axis. Both time and space are reinvented exclusively in the individual feelings and contemplations of the poet. They are as unique as the uniqueness and the only-ness of a man.
Keywords: Գրականագիտութիւն